Porous hard carbon derived from coconut biomass waste as electrode material for supercapacitor - Muhammadin Hamid; Indri Dayana; Habib Satria; Dadan Ramdan; Junaidi; Muhammad Fadlan Siregar; Dewi Sholeha; Juliaster Marbun; Hadi Wijoyo (JCIS Open)
The synthesis of porous hard carbon from coconut biomass waste using physical activation through pyrolysis and chemical activation with orange juice as an organic activator at varying temperatures, including 500 °C, 600 °C, and 700 °C, has been carried out. The purpose of this research is to develop materials for faradaic-type supercapacitor electrodes based on these temperature variations. Characterization and testing methods used include X-ray diffraction (XRD), scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET), cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS). BET analysis showed that the PHC-700 sample exhibited a relatively high specific surface area with porous characteristics and a narrow pore size distribution around 17–18 nm. The PHC-700 sample also exhibited the best electrochemical performance with a specific capacitance of 485.23 F/g and a total resistance of 24.29 Ω. GCD measurements revealed stable triangular curves, indicating good charge-discharge reversibility and confirming the superior capacitive behavior of PHC-700. The study confirmed that the higher the temperature used, the better the supercapacitor electrode obtained. This is evidenced by the pores on the surface that help improve the quality of the electrode and the XRD test results which are directly proportional to the increase in temperature. It is hoped that this research can enhance understanding of supercapacitor electrode applications.